2018
DOI: 10.12944/cwe.13.3.07
|View full text |Cite
|
Sign up to set email alerts
|

Land-Use and Land Cover Changes on the Slopes of Mount Meru-Tanzania

Abstract: The study of spatial land use and land change is inevitable for sustainable development of land use plans. Environmental transitions analysis was done in part of the land on the slopes of the foothills of Mount Meru in thirty (30) years’ time from 1986 to 2016 using satellite-derived land use/cover maps and a Cellular Automata (CA) spatial filter under IDRISI software environment and assessed the important land use changes. Also, the future land use for 2026 which is the next ten (10) years was simulated based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…As shown in (5), where the f ′ represents the derivative of the above pooling layer function (5). e k ζ ij is convolution kernel, the δ ζ+1 j is the weight parameters.…”
Section: Convolutional Neural Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in (5), where the f ′ represents the derivative of the above pooling layer function (5). e k ζ ij is convolution kernel, the δ ζ+1 j is the weight parameters.…”
Section: Convolutional Neural Networkmentioning
confidence: 99%
“…e use of land will undergo major changes over time, which requires a technology that can process land data in real time. Land is a very important resource for humans and even organisms, and it is the basis for human production, development, and survival [5]. e changes in land use directly affect the progress and development of human society and also have an important impact on the development and distribution of natural resources.…”
Section: Introductionmentioning
confidence: 99%
“…The current rates are higher than ever recorded [7]. Many studies have also shown that land use/cover changes influence the hydrology of watersheds [8][9][10][11]. Thus, evaluating the impact of land cover (LC) and climate changes on water resource availability is an important Earth 2021, 2, 225-247. https://doi.org/10.3390/earth2020014 https://www.mdpi.com/journal/earth challenge for the current hydrological science [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Since the water available is insufficient for economic use, urban dwellers extend to the nearby streams for easy access [9]. Rivers in the Arusha region pass through human settlements and downstream to areas with several human activities, including inefficiently treated effluent wastewater and inappropriate urban planning [10].…”
Section: Introductionmentioning
confidence: 99%